Design And Study Of Spinning Sea Wave Point Absorber - Joshua Wong, Jia Yi (Universiti Sains Malaysia, 2018)
Renewable energy sources are becoming more important when the world tries to ensure sustainability in energy generation for the future. With a potential to harness over 20,000TWh of electrical energy from the ocean, various types of energy converters were being developed. One of such energy converter is the point absorber which converts the potential and kinetic energy in the ocean wave motion into electricity. Though point absorber technology has been developed over the years, no research were conducted to study the effectiveness of utilizing a spinning motion for electricity generation in the point absorber instead of the conventional translational mechanism. The study of Spinning Sea Wave Point Absorber focuses on the understanding, design, fabrication and testing of a spiral gear mechanism implemented in a point absorber, conducted in a controlled wave tank. It aims to compare the Capture Width Ratio with conventional point absorbers as well as to identify the most effective lead angle within the spiral gear mechanism. A wave tank is constructed and the wave generated is characterized. With the wave characteristics, a point absorber is designed and fabricated. Through the experiments, the CWR recorded is compared to external reference and theoretical results. The CWR recorded using different lead angle for the spiral gear were compared to identify the most effective lead angle. The results showed that the tested spinning sea wave point absorber achieved a relatively low CWR compared with conventional results, with a maximum of 0.11% where conventionally it ranges from 7% to 31%. Such result can be attributed to the ineffective DC generator selected, presence of significant frictional force in the spiral gear mechanism, unconstricted motion of the buoy, softness of material used to fabricate the point absorber and lack of robustness in the design. The most effective lead angle identified is 55°, which falls in the middle of all the lead angles tested. It was able to generate a significant amount of electricity with a relatively low fluctuation in performance.